2014
DOI: 10.1016/j.virusres.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific antigenic epitope at N-terminal segment of enterovirus 71 (EV-71) VP1 protein and characterization of its use in recombinant form for early diagnosis of EV-71 infection

Abstract: Human enterovirus 71 (EV-71) is the main etiologic agent of hand, foot and mouth disease (HFMD). We sought to identify EV-71 specific antigens and develop serologic assays for acute-phase EV-71 infection. A series of truncated proteins within the N-terminal 100 amino acids (aa) of EV-71 VP1 was expressed in Escherichia coli. Western blot (WB) analysis showed that positions around 11–21 aa contain EV-71-specific antigenic sites, whereas positions 1–5 and 51–100 contain epitopes shared with human coxsackievirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, VP1 is usually used in the detection, identification, classification, and phylogenetic analysis of various EV71 genotypes. 160,161 Meanwhile, 3C protease plays an essential role in the life cycle of EV71. This protease cleaves the polyprotein precursor into constitutive proteins and interacts with several host factors that are essential for protein and nucleic acid synthesis.…”
Section: Dna Virusesmentioning
confidence: 99%
“…Therefore, VP1 is usually used in the detection, identification, classification, and phylogenetic analysis of various EV71 genotypes. 160,161 Meanwhile, 3C protease plays an essential role in the life cycle of EV71. This protease cleaves the polyprotein precursor into constitutive proteins and interacts with several host factors that are essential for protein and nucleic acid synthesis.…”
Section: Dna Virusesmentioning
confidence: 99%
“…Alignment analysis of amino acid sequences of EV-A71 showed that amino acid residues from 6-43 was highly conserved among all genotypes and sub-genotypes of EV-A71 and are different from strains of CV-A16 and Echovirus 6. When a VP1 truncated protein carrying the N-terminal antigenic epitope expressed as a GST-VP1 6-43 fusion protein was used in an indirect ELISA assay to capture anti-EV-A71 IgM in human sera, it showed a sensitivity of 77.8% and 100% specificity for early diagnosis of EV-A71 [40]. The sensitivity of this EV-A71-specific assay could perhaps be further improved by employing a direct IgM capture format.…”
Section: Immunoassaysmentioning
confidence: 99%
“…During translation, a single precursor polyprotein is synthetized and cleaved by proteases into four structural proteins (VP1–VP4) and seven functional proteins (2A–2C and 3A–3D) [ 17 , 18 ]. The majority of the viral epitopes are located on VP1, which is a key structural protein of EV71 [ 19 20 ]. Thus, VP1 is typically used as an indicator for the detection, identification, classification, and phylogenetic analysis of various EV71 genotypes [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%